2013
DOI: 10.5194/nhessd-1-1319-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New developments in ambient noise analysis to characterise the seismic response of landslide prone slopes

Abstract: Abstract. We report on new developments in the application of ambient noise analysis applied to investigate the dynamic response of landslide prone slopes to seismic shaking with special attention to the directional resonance phenomena recognised in previous studies. Investigations relying on the calculation of horizontal-to-vertical noise spectral ratio (HVNR) were carried out in the area of Caramanico Terme (central Italy) where an ongoing accelerometer monitoring on slopes with different characteristics off… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The interpretation of these data is not straightforward as for the cited nearly 2‐D case studies, in which the vibration motion at the first resonance frequency ( f 1) was systematically found to have the highest spectral amplitude and to be oriented perpendicularly to the main fracture set separating the unstable and stable sectors [e.g., Lévy et al, ; Burjánek et al, ; Del Gaudio et al, ; Bottelin et al, ]. The vibration directions are here complicated by the presence of two distinct unstable blocks, which are separated by a complex 3‐D fracture setting and constrained to a sloping basal discontinuity.…”
Section: Site Response: Ambient Seismic Noise and Earthquakessupporting
confidence: 90%
See 1 more Smart Citation
“…The interpretation of these data is not straightforward as for the cited nearly 2‐D case studies, in which the vibration motion at the first resonance frequency ( f 1) was systematically found to have the highest spectral amplitude and to be oriented perpendicularly to the main fracture set separating the unstable and stable sectors [e.g., Lévy et al, ; Burjánek et al, ; Del Gaudio et al, ; Bottelin et al, ]. The vibration directions are here complicated by the presence of two distinct unstable blocks, which are separated by a complex 3‐D fracture setting and constrained to a sloping basal discontinuity.…”
Section: Site Response: Ambient Seismic Noise and Earthquakessupporting
confidence: 90%
“…Furthermore, ambient vibration surveys have been recently applied to potentially unstable rock slopes for either investigation or monitoring purposes, showing the capability to detect both reversible and irreversible modifications within the rock mass that are driven by external factors and controlled by the fracture settings [ Larose et al, ]. Several previous studies demonstrated that the presence of spectral peaks in the seismic noise measured on prone‐to‐fall compartments could be associated with their resonance frequencies [e.g., Lévy et al, ; Burjánek et al, ; Del Gaudio et al, ; Bottelin et al, ]. This hypothesis is supported by the absence of similar peaks in the noise spectra recorded on the stable rock mass.…”
Section: Introductionmentioning
confidence: 58%
“…During the past decades, the effect of local soil condition is known to have caused serious damage during several earthquakes. Some well-known examples include the earthquake in Michoacan, Mexico, in 1985, Loma Prieta, California, USA, 1989, Roodbar, Iran, 1990, Chi-Chi, Taiwan, 1999, Bam, Iran, 2003 In general, site effect has introduced the effects of soils layers and underground topography which alter the specification of strong ground motion (Choobbasti et al 2013;Del Gaudio et al 2013). It is well accepted that, besides the earthquake magnitude and fault distance, local geological conditions, known as site effects, can impose significant influences on the earthquake ground motion at a given place (Rezaei et al 2015;Panzera et al 2013).…”
Section: Introductionmentioning
confidence: 99%